Desenvolvimento de biodetergentes utilizando biossurfactantes como matéria-prima - Barbosa, Silvanito Alves (2011)
The majority of surfactants commercially available is synthesized from petroleum, thus representing an important source of pollution, causing adverse biological effects to the aquatics organisms. In the detergent industries, despite of many trades available in the market are called as biodegradable and under the legislation actual, it's known that in real the actives components are tensoactives obtained by chemical and not by biochemical route. In other words, what occurred was only a change of the main active component alkylbenzene sodium sulphonate branched chain for one of linear chain, what in fact facilitated the molecular degradation by microorganisms, but not as much as compared to the natural surfactants. Arming to salve those problems, in this work we will show a development process of two biodetergents from biosurfactants that follow environmental appeal and available new alternatives products in the market, using a new technology which may be inserted promise of sustainable industrial development that give attention, specially, to the use of clean technologies. The purpose of this invention is to combine the main soap and synthetic detergent’s features providing an alternative to using of the latter, therefore it adds from the soap its higher biodegradability’s features and from the synthetic detergent its advantage on acting in a still efficient way, even when utilized in hard waters. Initially, were produced two biosurfactants called as liposan and rhamnolipid obtained from aerobic fermentation, using a Yarrowia lipolytica IMUFRJ 50682 yeast strain and another Pseudomonas aeruginosa INCQS 0588092 bacterium straim, respectively. After the analysis of the different experimental conditions, it was concluded that the pH 7.0, at temperature of 35°C with rotation of 150 rpm, were the main factor that influenced on the production of both biosurfactants. The response variables used were surface tension, the index E24, the production of biomass, biosurfactant production and consumption of substrate. After the separation and extraction of the liposan and the rhamnolipid, it was held the modification of the two molecules by a chemical reaction and the biodetergents were formulated adding the adjuvant agents and completing the final volume with distilled water. The efficiency of the biodetergents was evaluated comparing the viscosities from a sample of crude oil with a produced water emulsion/oil containing the biodetergents, where it was verified a reduction on the viscosity, about 8% for the biodetergent 1 derived from the liposan and 36% for the biodetergent 2 derived from the rhamnolipid. It was observed from the analysis of the DSC that the developed biodetergents didn’t show any physico-chemical change when dissolved in samples of distilled water and compared to the produced water, concluding that both show good thermal stability and it wasn’t detected any chemical interaction, on the studied thermal range, between the biodetergents and the present salts in great quantity in the produced water, showing also a good tolerance to ionic strength. Regarding the capacity to produce foam and remove dirt in tissues and dishes both produced biodetergents showed foaming power and detergent action similar when compared to the synthetic detergent commercial. Therefore, it’s concluded that the produced biodetergents show good surfactant and emulsification capacity compared to the chemical synthetic surfactants, maybe being used in substitution themselves for the presented advantages.